Impact of Evidence-Based Stroke Care on Patient Outcomes: A Multilevel Analysis of an International Study - Venturelli, Paula Munoz; Li, Xian; Middleton, Sandy; Watkins, Caroline; Lavados, Pablo M.; Olavarria, Veronica V.; Brunser, Alejandro; Pontes-Neto, Octavio; Santos, Taiza E. G.; Arima, Hisatomi; Billot, Laurent; Hackett, Maree L.; et al. (Wiley-Blackwell, 2019)
Background-The uptake of proven stroke treatments varies widely. We aimed to determine the association of evidence-based processes of care for acute ischemic stroke (AIS) and clinical outcome of patients who participated in the HEADPOST (Head Positioning in Acute Stroke Trial), a multicenter cluster crossover trial of lying flat versus sitting up, head positioning in acute stroke. Methods and Results-Use of 8 AIS processes of care were considered: reperfusion therapy in eligible patients; acute stroke unit care; antihypertensive, antiplatelet, statin, and anticoagulation for atrial fibrillation; dysphagia assessment; and physiotherapist review. Hierarchical, mixed, logistic regression models were performed to determine associations with good outcome (modified Rankin Scale scores 0-2) at 90 days, adjusted for patient and hospital variables. Among 9485 patients with AIS, implementation of all processes of care in eligible patients, or defect-free care, was associated with improved outcome (odds ratio, 1.40; 95% CI, 1.18-1.65) and better survival (odds ratio, 2.23; 95% CI, 1.62-3.09). Defect-free stroke care was also significantly associated with excellent outcome (modified Rankin Scale score 0-1) (odds ratio, 1.22; 95% CI, 1.04-1.43). No hospital characteristic was independently predictive of outcome. Only 1445 (15%) of eligible patients with AIS received all processes of care, with significant regional variations in overall and individual rates. Conclusions-Use of evidence-based care is associated with improved clinical outcome in AIS. Strategies are required to address regional variation in the use of proven AIS treatments.
Keywords: acute stroke care; multilevel analysis; outcome; quality